Bakteri Endofit F4 dari Daun Pepaya (Carica papaya L): Potensinya sebagai Penghasil Enzim Ekstraseluler - Sarjono, Purbowatiningrum Ria; Ismiyarto, Ismiyarto; ngadiwiyana, Ngadiwiyana; Prasetya, Nor Basid Adiwibawa (Universitas Diponegoro, 2022)
AbstractPapaya leaves are known to have antibacterial activity, so the endophytic bacteria on the papaya leaves are thought to have antibacterial activity. Previous studies have obtained 5 isolates of endophytic bacteria from papaya leaves, including F1, F2, F3, F4 and F5. Endophytic bacteria F1, F3, and F5 have known antibacterial activity, while endophytic bacteria F4 have not yet explored their activity in producing extracellular enzymes, so that in this study a qualitative test of extracellular enzymes was carried out on endophytic bacteria F4. The purpose of this study was to obtain confirmation of morphology, qualitative phytochemical data, and the ability to produce extracellular enzymes lipase, cellulase, protease and amylase from endophytic bacteria F4.The results obtained were F4 bacterial isolates white, round and smooth rounded edges which were gram positive with single cell morphology and the shape is bacillus (stems). F4 bacteria have the potential to contain amylase and protease extracellular enzymes.